1980
DOI: 10.1073/pnas.77.2.1059
|View full text |Cite
|
Sign up to set email alerts
|

Increased mutation in crosses between geographically separated strains of Drosophila melanogaster.

Abstract: Mutator activity associated with the common male recombination (MR) chromosomes in Drosophila melanogaster appears to be suppressed in natural populations. Crosses between geographically separated populations, however, lead to the release of mutator activity as measured by a significant increase in visible mutations. Such an increase in mutation in hybrid individuals may be a powerful factor in inducing or releasing variation in nature, and in more extreme instances may contribute to the separation of microdif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
1
19
0
4
Order By: Relevance
“…If insertional sites are potentially deleterious, selection could favour any of a wide variety of means of regulation, and genetic analysis of the hybrid dysgenesis system in Drosophi!a melanogaster offers a powerful way to study them. For example, both mutation and chromosome breakage studies confirm that mutator activity is decreased or totally suppressed within a strain, but it is released from suppression in certain crosses between strains (Woodruff et al, 1979;Thompson and Woodruff, 1980). In addition, while mutator factors can be mapped, the large difference between mutation rates in reciprocal crosses shows that the system also has an extra-chromosomal component.…”
Section: Nomadic Dna and Mutation Ratesmentioning
confidence: 93%
“…If insertional sites are potentially deleterious, selection could favour any of a wide variety of means of regulation, and genetic analysis of the hybrid dysgenesis system in Drosophi!a melanogaster offers a powerful way to study them. For example, both mutation and chromosome breakage studies confirm that mutator activity is decreased or totally suppressed within a strain, but it is released from suppression in certain crosses between strains (Woodruff et al, 1979;Thompson and Woodruff, 1980). In addition, while mutator factors can be mapped, the large difference between mutation rates in reciprocal crosses shows that the system also has an extra-chromosomal component.…”
Section: Nomadic Dna and Mutation Ratesmentioning
confidence: 93%
“…A similar mating scheme as described above was used successfully in earlier assays for the occurrence of mutation clusters in several laboratories (17,18,(25)(26)(27). It was estimated that lethal or nearly lethal mutations identified by the assay span over about 1,200 genes.…”
Section: Methodsmentioning
confidence: 99%
“…As an indication of the possible impact of hybrid release on the rate of genetic change in nature, Woodruff and Thompson (1982b, and in preparation) have observed that the progeny from 25 of 90 crosses between natural population lines of D. melanogaster have a significantly higher frequency of spontaneous lethal mutations than do the base populations, and similar values have been observed for spontaneous breakage in hybrid progeny. One consequence of the intraspecific release of mutator activity is that high levels of rare genetic variants observed in hybrid zones (Hunt and Selander, 1973;Avise and Smith, 1974;Kilpatrick and Zimmerman, 1976;Gould and Woodruff, 1978;Sage and Selander, 1979;Smith, 1979;Moran et a!., 1980;Greenbaum, 1981;Hafner, 1982;Peters, 1982;Barton et aL, 1983) may be due to increased rates of mutation (Woodruff et aL, 1979;Thompson and Woodruff, 1980), although intragenic recombination could also explain these variants (Golding and Strobeck, 1983). Support for increased rates of mutation as the cause of the increased genetic variation in hybrid zones comes from the observation that high frequencies of novel chromosome re-arrangements are observed in hybrid zones of grasshoppers and the re-arrangements are derived only from hybrid parents (Shaw et aL, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…For example, hybridisation among migrants in the large-density winery population might be expected to increase mutation rates by the documented intraspecific hybrid release of mutator activity (Thompson and Woodruff, 1980;Woodruff et a!., 1980;Shaw et a!., 1983). As an indication of the possible impact of hybrid release on the rate of genetic change in nature, Woodruff and Thompson (1982b, and in preparation) have observed that the progeny from 25 of 90 crosses between natural population lines of D. melanogaster have a significantly higher frequency of spontaneous lethal mutations than do the base populations, and similar values have been observed for spontaneous breakage in hybrid progeny.…”
Section: Discussionmentioning
confidence: 99%